Free rides to diving sites: the risk of marine non-indigenous species dispersal. (1st June 2020) - Parretti, Paola; Canning-Clode, João; Ferrario, Jasmine; Marchini, Agnese; Botelho, Andrea Z.; Ramalhosa, Patrício; Costa, Ana C.
Abstract: The detection of marine non-indigenous species (NIS) continues to increase worldwide, and this is also the case in the Portuguese islands of the Azores and Madeira. Considering that the major vector of NIS introductions in these archipelagos is marine traffic and given the absence of legislation on hull biofouling management, the number of NIS introduced in the marinas of these archipelagos is also expected to grow. Moreover, tourism intensification has brought more attention on seascapes, resulting in an increased number of recreational divers in these islands. The potential impact of recreational boating as a vector of NIS secondary spread has been already addressed, but no studies have been conducted yet on the role of diving-boats in transport and local dispersion of NIS, e.g. from marinas to diving sites. In this context, we developed a fuzzy inference system to assess the risk of a diving site to receive NIS transported by diving boats. Furthermore, we have validated the model with observational data. In particular, our "free-ride" model is composed by three levels: Level 1 evaluates the risk of each marina to act as NIS source. Level 2 assesses the risk of a diving boat to transport NIS to a diving site. Finally, Level 3 calculates the risk of a diving site to receive NIS. Input variables were collected from questionnaire surveys and from environmental monitoring data. A strong positive relationship was found between the predicted risk value and the actual number of NIS identified in the diving site suggesting the efficiency of the "free-ride" model. Results have revealed that diving sites inside marine protected areas (MPAs) displayed a higher risk to receive NIS than those located outside MPAs highlighting the need to undertake management action to mitigate the transport of NIS by fouling. The "free-ride" model represents a valuable method to identify: "high-risk" marinas, diving-boats and diving sites. Our model enables to prioritize actions for diving centres to control local spreading of NIS and promote conservation of marine habitats. Graphical abstract: Image 1 Highlights: Assessment of the spreading risk of marine non-indigenous species by diving boats. Elaboration of a fuzzy model composed by three levels of risk. Diving sites located inside MPAs have higher predicted risk than those outside. The model is successfully tested with observational data.